Organizational Learning and Job Satisfaction of Employees in Financial Sectors - Devakota, Surya Prasad; Bhattarai, Ganesh (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates the impact of organizational learning on employee job satisfaction in Nepal's banking sector, aiming to fill a critical research gap in this context. Specifically, it explores how workplace learning environments influence job satisfaction and examines the moderating roles of demographic factors such as gender, age, and educational qualifications. Adopting a causal research design, the study utilized a non-probability judgmental sampling method, collecting 425 valid responses. The survey instrument, divided into demographic details, job satisfaction, and organizational learning components, was developed from established studies and validated through pilot testing. Statistical tools were employed for data evaluation, including reliability analysis, regression, and principal component analysis. The results confirmed the survey's reliability, with Cronbach's Alpha values of 0.713 for job satisfaction and organizational learning. Two principal components explained 79.32% of the total variance. Findings revealed a positive impact of organizational learning on job satisfaction, with minor gender-based differences, except in perceptions of teamwork. Employees with over 20 years of experience reported higher satisfaction with learning culture and collaboration. The study's novelty is identifying organizational learning as a critical factor in enhancing job satisfaction, emphasizing the importance of fostering knowledge sharing and a supportive workplace culture. Its implications suggest that management strategies promoting learning opportunities can significantly improve employee morale, performance, and organizational competitiveness.